Nutrition education program and knowledge, attitudes, and behavior of Iranian students: A clinical trial - Arezoo Rasooli; Farkhonde Amin-Shokravi; SedigheSadat Tavafian (Tehran University of Medical Sciences, 2015)
Background & Aim: Dietary behavior modification has an important effect on chronic disease occurrence. This study aimed to examine the effects of an education program on nutritional knowledge, attitude, and behavior among female students studying in Bojnord, Iran. Methods & Materials: This was a clinical trial that was conducted in 2009. Of all secondary schools, 2 classes were randomly selected from which 115 students were recruited and randomly divided into intervention group (n = 55) or control group (n = 60). The intervention program was administered to the intervention group, whereas the other group just received routine education. Data were collected at baseline, and after 45 days and 360 days of follow up via a self-administered questionnaire regarding knowledge, attitude, and practice variables. Repeated measure ANOVA was used to analyze data. Results: As the results showed, there were significant differences within each group over time in terms of knowledge, attitude, and behavior (P < 0.001). Furthermore, the two groups, regardless of time, were different in all studied variables (P < 0.001) and also the interaction between time and group were significantly different regarding the three studied scales (P < 0.001). Conclusion: This study indicated that the designed educational program could improve the knowledge, attitude, and nutrition behavior of female students of Birdjand up to 12 months. Therefore, this program could be conducted in primary schools of Bojnord city to improve nutrition behavior of the students.